2019
DOI: 10.1016/j.jaerosci.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of air humidity on particle filtration performance of a pulse-jet bag filter

Abstract: A B S T R A C TA pulse-jet bag filter, representative of those implemented in waste incineration plants for flue gas treatment, was studied at laboratory scale to evaluate the influence of air humidity on the filtration performance. Several cycles of clogging/unclogging were performed with non-hygroscopic submicronic particles with a nanosized fraction with on-line cleaning at operating conditions as similar as possible to those found in the flue gas treatment of waste incineration plants (150°C -73 g/m 3 of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Blocking at high humidity [68][69][70][71][72][73] Electrostatic precipitator Adsorption of charged dust particles by electrodes.…”
Section: High Dust Removal Efficiency and Stable Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking at high humidity [68][69][70][71][72][73] Electrostatic precipitator Adsorption of charged dust particles by electrodes.…”
Section: High Dust Removal Efficiency and Stable Operationmentioning
confidence: 99%
“…When the ambient humidity is too high, it has a certain impact on the performance of the bag filter. Boudhan[72] et al found that when the gas at the inlet contains water vapor, the capillary condensation of water makes the powder layer more compact, which accelerates the increase in the pressure difference and reduce the life of the filter bag. For a pulse bag filter, the performance of the air nozzles affects the dust removal effect.…”
mentioning
confidence: 99%
“…Steel, cement, mining and other industrial processes can produce a large amount of dust, and the problem of severe air pollution caused by dust emissions has attracted great attention [1][2][3]. Bag dust collector is commonly recognized as the most effective method to deal with particulates such as smoke and dust.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the bag filter system is the most commonly applied in various industrial fields. For example, such systems have been installed in municipal garbage incineration facilities and coal-fired power plants [1][2][3][4][5][6], and their primary role is to exhibit enough mechanical strength to collect dust particles and withstand the related pressure drop. Therefore, the structure of bag filters, particularly those made of nonwoven fabric, consist of densely packed, relatively thick fibers [7,8].…”
Section: Introductionmentioning
confidence: 99%